1984
DOI: 10.1128/aac.25.3.319
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin, a quinolone carboxylic acid compound active against aerobic and anaerobic bacteria

Abstract: The in vitro activity of ciprofloxacin, a quinolone-carboxylic acid derivative, was compared with those of norfloxacin, cefotaxime, cephalexin, ceftazidime, moxalactam, amoxicillin, and methicillin and other agents, as appropriate. The MICs of ciprofloxacin for 90% of members of the family Enterobacteriaceae and for Pseudomonas aeruginosa, Neisseria spp., and Bacteroides fragilis were between 0.005 and 0.8 ,ug/ml, whereas streptococci and staphylococci were all inhibited by c6.3 p,g/ml. Ciprofloxacin was 4-to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
147
5
2

Year Published

1985
1985
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(165 citation statements)
references
References 10 publications
11
147
5
2
Order By: Relevance
“…Several reports are available on the mechanism of quinolone resistance in either E.coli or K.pneumoniae or even both or quinolone resistance in ESBL producing bacteria; however, no report is available on the actual resistance of nalidixic acid and ciprofloxacin in these two isolates [29][30][31][32][33][34][35] , except few published studies on urinary isolates, [36][37][38][39][40] whereby low prevalence has been reported as compared to our study. Study performed in our neighboring country reported 17% and 38% of E. coli isolates obtained from uncomplicated and complicated UTI respectively, were found resistant to ciprofloxacin.…”
Section: Quinolone Esbl Resistance and Integronscontrasting
confidence: 48%
“…Several reports are available on the mechanism of quinolone resistance in either E.coli or K.pneumoniae or even both or quinolone resistance in ESBL producing bacteria; however, no report is available on the actual resistance of nalidixic acid and ciprofloxacin in these two isolates [29][30][31][32][33][34][35] , except few published studies on urinary isolates, [36][37][38][39][40] whereby low prevalence has been reported as compared to our study. Study performed in our neighboring country reported 17% and 38% of E. coli isolates obtained from uncomplicated and complicated UTI respectively, were found resistant to ciprofloxacin.…”
Section: Quinolone Esbl Resistance and Integronscontrasting
confidence: 48%
“…Chemically it is 1-cyclopropyl-6-fluoro-1,4-dihydro-4-oxo-7-(1-piperazinyl)-3-quinolinecarboxylic acid] [3,5,11]. It was found to be more active against enterobacteriaceae than the older drugs of this class, such as nalidixic acid, with minimum inhibitory concentrations ranging from 0.008 to 2.0 mg/l [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Both drugs are well absorbed orally, have serum half-lives of 8.6 and 3.9 h, respectively, and reach concentrations in serum well above the MIC for many bacterial species (3, 6). Extensive in vitro studies have shown that ciprofloxacin has a MIC90 of -1 g/ml, whereas pefloxacin has a MIC90 of .2 ,ug/ml for many of the above-mentioned bacteria (2,5,14). It is of special interest that both of these antimicrobial agents are highly active against Pseudomonas aeruginosa, including multiply drug-resistant strains (2, 11).…”
mentioning
confidence: 99%